Polyphonic Mysticism: Bakhtinian Dialogism and the Spiritual Voice in Elif Shafak’s the Forty Rules of Love - Arshad, Amina (ACADEMIA International Journal for Social Sciences, 2025)
This paper examines Elif Shafak’s The Forty Rules of Love through a Bakhtinian framework to highlight the novel's polyphonic construction of mysticism. While the existing literature largely focuses on the Sufi sentiment and intertextual layering of the text, it often overlooks the dialogic structure which shapes the spiritual meaning. By employing Bakhtin’s concepts of heteroglossia, chronotope and dialogism, this study aims to explore how Shafak subverts the notion of a single, overwhelming mystical truth by emphasizing plurality, narrative tension and temporal shift. The objective of this research is to interrogate the novel’s intertwined structure, connecting historical space with contemporary world, to disclose the profound coexistence of competing ethical, emotional and cultural voices that overall shape the spiritual understanding of the text. By situating mysticism as emergent, relational and inherently contested, the study demonstrates how narrative form itself enacts spiritual inquiry, thus inviting readers to actively participate in meaning-making process. This analysis extends the literary and Sufi studies by presenting the novel’s role  in conceptualizing mysticism as dialogic and polyphonic.